G4Hunter web application: a web server for G-quadruplex prediction - Brázda, Václav; Kolomazník, Jan; Lýsek, Jiří; Bartas, Martin; Fojta, Miroslav; Šťastný, Jiří; Mergny, Jean-Louis (Bioinformatics (Oxford, England), 2019)
MOTIVATION: Expanding research highlights the importance of guanine quadruplex structures. Therefore, easy-accessible tools for quadruplex analyses in DNA and RNA molecules are important for the scientific community. RESULTS: We developed a web version of the G4Hunter application. This new web-based server is a platform-independent and user-friendly application for quadruplex analyses. It allows retrieval of gene/nucleotide sequence entries from NCBI databases and provides complete characterization of localization and quadruplex propensity of quadruplex-forming sequences. The G4Hunter web application includes an interactive graphical data representation with many useful options including visualization, sorting, data storage and export. AVAILABILITY AND IMPLEMENTATION: G4Hunter web application can be accessed at: http://bioinformatics.ibp.cz. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: internet; sekvenční analýza DNA; Sequence Analysis, DNA; Internet; G-kvadruplexy; počítače; software; G-Quadruplexes; guanin; Guanine; Software; DNA; Computers